2012
DOI: 10.1002/cbic.201100743
|View full text |Cite
|
Sign up to set email alerts
|

A New Chemical Handle for Protein AMPylation at the Host–Pathogen Interface

Abstract: Tagging protein AMPylation: A new chemical reporter for AMPylation, recently identified as a key post‐translational modification during bacterial infection, is a robust tool for detecting and identifying AMPylated proteins in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The distribution of these candidate substrates' molecular weights agreed with previous findings using gel-based AMPylation assays (Fig. 2E, 2F) (2,3,12,14). The annotations showed that many of the VopS and IbpAFic2 substrates were RhoGTPases, 8 and 7, respectively.…”
Section: Fig 2 Global Identification Of Substrates For Vops and Ibpsupporting
confidence: 88%
See 1 more Smart Citation
“…The distribution of these candidate substrates' molecular weights agreed with previous findings using gel-based AMPylation assays (Fig. 2E, 2F) (2,3,12,14). The annotations showed that many of the VopS and IbpAFic2 substrates were RhoGTPases, 8 and 7, respectively.…”
Section: Fig 2 Global Identification Of Substrates For Vops and Ibpsupporting
confidence: 88%
“…With these efforts combined, four potential new VopS substrates have been identified (SCCA2, NAGK, NME1, and PFKP), though not yet confirmed. These approaches might miss substrates because of temporal and spatial expression or low abundance in cell lysate, poor recognition by the capture molecules or loss during pull-down procedures (12,14).…”
mentioning
confidence: 99%
“…Though target enrichment advanced with the introduction of an antibody raised against AMPylated threonine , tyrosine‐modified peptides, and proteins would escape purification. Another promising step forward was recently presented by a strategy utilizing a functionalized ATP analog that can be trapped by an azide alkyne cycloaddition (also known as CLICK chemistry approach) to enrich for modified proteins . Yet, the modification of ATP goes along with changes in size and electron density of the substrate, which might impair binding to the substrate‐binding site of Fic proteins .…”
mentioning
confidence: 99%
“…In contrast, there are only scare data about the SELO's function and protein substrates (Sreelatha et al, 2018). Several complementary strategies were introduced to analyze protein AMPylation, including isotopically labeled adenosine probes (Pieles et al, 2014), radioactively labelled adenosine nucleotides, antibodies (Kingdon et al, 1967;Yarbrough et al, 2009), microarrays (Yu and LaBaer, 2015), N 6 -biotin modified ATP (Sreelatha et al, 2018), and N 6 -propargyl adenosine 5'-O-triphosphate (N6pATP) or phosphoramidate (Broncel et al, 2012;Grammel et al, 2011;Kielkowski et al, 2020bKielkowski et al, , 2020a. We have recently developed a chemical proteomic approach, which allows high-throughput screening of protein AMPylation and comparison of the AMPylation levels between different conditions.…”
Section: Introductionmentioning
confidence: 99%